The added value of f‐TAPSE in the surveillance of pregnancies complicated by fetal and placental tumors. (10th July 2017) - Perlman, Sharon; Messing, Baruch; Salem, Yishay; Porat, Shiran; Achiron, Reuven; Gilboa, Yinon
Abstract: Introduction: Fetal and placental tumors are associated with high prevalence of obstetrical complications and poor fetal outcome. The aim of our study was to assess the added value of serial fetal Tricuspid Annular Plane Systolic Excursion (f‐TAPSE) measurements for monitoring cardiac function in cases of fetal and placental tumors. Methods: Serial measurements of f‐TAPSE were performed prospectively in fetuses referred for fetal and placental tumors. The patients were followed longitudinally every 2 weeks. In each visit, tumor measurements, Doppler flow indices, fetal cardiothoracic index and measurements of f‐TAPSE were performed. Results: During the study period, 11 fetuses were followed prospectively: seven chorioangiomas and four fetal tumors. In eight cases, the f‐TAPSE was measured in the upper range for gestational age. In three cases of small or poorly vascularized tumors, the measurements were within the 50th percentile for gestational age. In two cases who presented with elevated f‐TAPSE, a regression in the f‐TAPSE percentile was observed: in the first case, the tumor regressed; however, in the second case, the f‐TAPSE pseudo normalized and was followed by cardiac decompensation. Conclusions: f‐TAPSE may serve as a complementary tool for assessing tumors associated hyper‐dynamic state and early diagnosis of cardiac decompensation. © 2017 John Wiley & Sons, Ltd. Abstract : What is already known about this topic? Fetal and placental tumors are associated with high prevalence of obstetrical complications and poor fetal outcome. Close surveillance of fetal cardiac function is necessary to establish prenatal and delivery management in order to decrease adverse outcome. What does this study add? Serial measurements of the f‐TAPSE offer a quantitative tool sensitive to the relationship between the fetal myocardium and the degree of shunting within the low resistance tumor vasculature. f‐TAPSE offers a quantitative tool for serial follow‐up throughout gestation and may aid in early diagnosis of fetal cardiac decompensation.